Sculptors and sculptures in the Viceroyalty of Peru at the beginning of the Baroque period - Porres Benavides, Jesús (2018)
The objective of this article is to describe the flow of artists and sculptural works from Spain to the new territories incorporated into the Crown of Castile, with a special focus on the Viceroyalty of Peru. A series of religious sculptures are analized in the city of Lima, as well as in some Chilean cities. Likewise, the type of works that were sent or ordered during that time is studied based on documentation of different archives.